The respiratory impact of novel therapies for spinal muscular atrophy. Issue 4 (2nd November 2020) - Paul, Grace R.; Gushue, Courtney; Kotha, Kavitha; Shell, Richard
Abstract: The phenotype of spinal muscular atrophy (SMA) has been changing with the recent availability of three FDA‐approved treatments: intrathecal nusinersen, intravenous onasemnogene abeparvovec‐xioi, and enteral risdiplam. The degree of improvement in muscle strength and respiratory health varies with SMA genotype, severity of baseline neuromuscular and pulmonary impairment, medication used, and timing of the first dose. A spectrum of pulmonary outcomes has been reported with these novel medications when used early and in conjunction with proactive multidisciplinary management of comorbidities. In this review, we summarize the reported impact of these novel therapies on pulmonary well‐being and the improving trajectory of pulmonary morbidity, compared to the natural history of SMA. The importance of ongoing clinical monitoring albeit the improved phenotype is reiterated. We also discuss the limitations of the current SMA‐therapy trials and offer suggestions for future clinical‐outcome studies and long‐term monitoring.